Pengaruh Konsentrasi Polyethylene Glycol (PEG) dan Jenis Media Simpan terhadap Daya Simpan Benih Kakao (Theobroma cacao L.) - Noviani, Made; Darmawati, Ida Ayu Putri; Mayun, Ida Ayu (Fakultas Pertanian Universitas Udayana, 2023)
Effect of Polyethylene Glycol (PEG) Concentration and Type of Storage Media on the Shelf Life of Cocoa Seeds (Theobroma cacao L.). Cocoa seeds are recalcitrant seeds that deteriorate quickly, so special treatment is needed with the PEG concentration and type of storage media. The study started in October – November 2021. The aim of the study was to obtain the best concentration of PEG-6000 and the best type of storage media and to determine the interaction of treatments. The study used a Factorial Completely Randomized Design (CRD). The first factor is the concentration of PEG-6000 (P) with 4 levels: P0 = PEG 0% (control); P1 = PEG 15%; P2 = PEG 30% and P3 = PEG 45%. The second factor is the type of storage media (S) with 3 levels: Sk = without storage media (control); Sg = Sawdust and Ss = Husk Charcoal. The results showed that the concentration of PEG (P) had a very significant effect on the variables of healthy seeds, moldy seeds in storage and germination rate. The best results were found at PEG 45% with the highest germination rate of 10.19 sprouts/day. The type of storage media (S) had a very significant effect on the variables of healthy seeds, germinated seeds, moldy seeds in storage, seed moisture content after storage and germination rate. The highest results on husk charcoal media in seed moisture content variable after storage was 39.11%, seeds germination in the nursery was 9.70%, germination rate was 11.98 sprouts/day and hypocotyl length was 2.54 cm and there was an interaction between healthy seeds, germinated seeds and moldy seeds in storage. The best results were found at a concentration of PEG 45% with husk charcoal (P3Ss) media with the highest result of healthy seeds in storage at 9.77% and germination of seeds in storage at the lowest 0.71%.